The comorbidity of fetal alcohol syndrome and sleep apnea/hypopnea syndrome in a 7‑year-old girl (a clinical case) - K. D. Yakovleva; O. V. Alekseeva; N. A. Shnayder; D. R. Sidorenko; D. V. Dmitrenko (Русский журнал детской неврологии)
Fetal alcohol syndrome is the result of prenatal effect of alcohol on the fetus and manifests as disorders of neural and mental development and various congenital developmental disorders leading to comorbid diseases. Among congenital developmental disorders for the pathology, adenotonsillar pathology was described. Narrowing of the nasopharyngeal opening, faciomaxillary dysmorphias and muscle hypotony can lead to sleep apnea syndrome. The article presents a clinical case of fetal alcohol syndrome and sleep apnea in a 7‑year-old girl with multiple developmental disorders born form alcohol-abusing mother. Breathing abnormalities during sleep must be differentiated per character and cause. Cardiorespiratory monitoring is used to diagnose respiratory abnormalities, the results determine patient management tactics. Interdisciplinary approach to observation and treatment of a child with fetal alcohol syndrome is necessary to increase the effectiveness of rehabilitation measures and patient’s quality of life.